A Novel Eco-Friendly Process for the Synthesis and Purification of Ascorbyl-6-Oleates - Ha-Eun Ji; Se-Young Kim; Heejin So; Vivian Prayitno; Ki-Teak Lee; Jung-Ah Shin (Foods)
Commercial ascorbyl-6-O-esters (AEs) are composed of saturated fatty acids with relatively high melting points, resulting in limited solubility in lipophilic media. Therefore, a lipase-catalysed synthesis and purification method for ascorbyl-6-O-oleate (AO) was proposed in this study. The esterification synthesis (i.e., bonding of oleoyl group to ascorbic acid) rate was 19.7% using acetone as the reaction solvent. The transesterification synthesis (i.e., exchange of acyl group with oleic acid (OA) in ascorbyl-6-O-palmitate (AP)) rate increased to 73.8% (AP:OA = 1:3, molar ratio). The esterification product was purified sequentially by liquid–liquid extraction using ethyl acetate and water, followed by hexane and acetonitrile, resulting in 94.8 area% AO confirmed by HPLC. When acetonitrile was replaced with 90% methanol, AO achieved 97.2 area%. Similarly, the transesterification product showed 94.3 area% AEs (AP:AO = 8.9:91.1) after recrystallisation and liquid–liquid extraction. Finally, all purified AO revealed peaks corresponding to the hydroxyl groups at the C-2 and C-3 carbons (11.10 and 8.41 ppm, 1H-NMR), whereas OA selectively esterified at the C-6 carbon (13C-NMR). FT-IR confirmed the presence of the ester bond (1733 cm−1) and olefin structure (3006 cm−1) of OA, and LC-ESI-MS/MS identified AO peaks at m/z 439.3. DSC analysis showed broad endothermic curves at 23.1–46.7 °C when the purified AO samples were pre-cooled at −25 °C.